Association between received treatment elements and satisfaction with care for patients with knee osteoarthritis seen in general practice in Denmark - Linda Baumbach; Donna Ankerst; Ewa M. Roos; Lillemor A. Nyberg; Elizabeth Cottrell; Jesper Lykkegaard (Taylor & Francis Group, 2021)
Objective While education, exercise, and weight reduction when indicated, are recommended first-line treatments for knee osteoarthritis patients, they remain poorly implemented in favour of pain killer treatment, imaging and referral to surgery. A reason could be that patients are more satisfied with receiving these adjunctive treatment elements. This study aimed to investigate the associations between the received elements of care and the patient's satisfaction with the care for knee osteoarthritis in general practice. Design Cross-sectional study. Setting A Danish general practice. Subjects All consecutive patients ≥30 years of age who consulted the general practitioner (GP) with chronic knee complaints during 18 months and who replied to a mailed questionnaire (n = 136). Main outcome measures The questionnaire addressed patient's knee-related quality of life, and overall satisfaction with care, as well as reception of seven types of information, which are known quality indicators. Information on reception of adjunctive treatment elements was obtained from electronic medical records. Results Patient satisfaction (versus neutrality/dissatisfaction) was positively associated with reception of information on: physical activity and exercise (relative risks [RR] 1.38, 95% bootstrap percentile interval [BPI] 1.02-4.33), and the relationship between weight and osteoarthritis (1.38, 1.01-4.41). No significant associations were found for the five remaining types of information and all the adjunctive treatment elements. Conclusion Providing information as education to patients with knee osteoarthritis as part of the treatment is positively associated with satisfaction with care.KEY POINTS General practitioners worry about the doctor-patient relationship when addressing recommended lifestyle changes. However, this study revealed: •Patients in general practice with knee osteoarthritis are satisfied with care after having received information on lifestyle changes, such as exercise and the relationship between weight and osteoarthritis. •Patient satisfaction was not associated with the reception of adjunctive treatment elements for osteoarthritis.